2024
DOI: 10.1039/d3nj03005a
|View full text |Cite
|
Sign up to set email alerts
|

Fish scale derived hydroxyapatite incorporated 3D printed PLA scaffold for bone tissue engineering

N. G. Thomas,
Y. B. Dalvi,
N Fijol
et al.

Abstract: Bone defect repair, particularly in the alveolar region, remains a significant hurdle in periodontics. In recent years, the spotlight in regenerative medicine has fallen on 3D-printed bone scaffolds, especially those...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…However, it is necessary to mention that the addition of the polycaprolactone (PCL) decreased the degradation rate. Furthermore, Thomas et al [ 45 ] found that an HA-incorporated 3D-printed PLA scaffold showcased compressive strength (13.4 ± 5.53 MPa) adequate for future in vivo evaluation. In this regard, synthetic PLA polymer Lactoprene ® 7415 was a material of choice in the presented study, due to its strictly determined mechanical properties and degradation rate.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is necessary to mention that the addition of the polycaprolactone (PCL) decreased the degradation rate. Furthermore, Thomas et al [ 45 ] found that an HA-incorporated 3D-printed PLA scaffold showcased compressive strength (13.4 ± 5.53 MPa) adequate for future in vivo evaluation. In this regard, synthetic PLA polymer Lactoprene ® 7415 was a material of choice in the presented study, due to its strictly determined mechanical properties and degradation rate.…”
Section: Resultsmentioning
confidence: 99%